2016
DOI: 10.1038/jhh.2016.63
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic detection of hypertensive left atrial enlargement in the presence of obesity: re-calibration against cardiac magnetic resonance

Abstract: Left atrial enlargement (LAE) has adverse prognostic implications in hypertension.We sought to determine the accuracy of 5 ECG criteria for LAE in hypertension relative to cardiac magnetic resonance (CMR) gold-standard, and investigate the effect of concomitant obesity. 130 consecutive patients (age: 51.4 ± 15.1 years, 47% male, 51% obese, systolic blood pressure: 171 ± 29mmHg, diastolic blood pressure: 97 ± 15mmHg) referred for CMR (1.5T) from a tertiary hypertension clinic were included. Patients with concom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
6
1
Order By: Relevance
“…Rodrigues et al also demonstrated higher specificity than sensitivity of ECG criteria, but the differences between sensitivity and specificity were larger than in our study. Contrary to our study, the authors observed higher specificity for the lead II than the lead V1 criterion [91% vs. 81%] [15] . They also observed that obesity was a strong attenuation factor for specificity.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Rodrigues et al also demonstrated higher specificity than sensitivity of ECG criteria, but the differences between sensitivity and specificity were larger than in our study. Contrary to our study, the authors observed higher specificity for the lead II than the lead V1 criterion [91% vs. 81%] [15] . They also observed that obesity was a strong attenuation factor for specificity.…”
Section: Discussioncontrasting
confidence: 53%
“…Previous studies comparing electrocardiographic criteria with CMR for LA size assessment in other patient populations produced results similar to ours. In the majority of these studies the prevalence of LA enlargement by CMR was much lower than in ECG and varied between 20 and 30% [14][15][16] . It was higher only in the study by Burekaam et al, but the authors decided to choose a lower cut-off value for LA enlargement as compared to our and other studies [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the authors did not compare various ECG criteria for LAE in order to determine which index had the best accuracy. Other investigators used different imaging methods for evaluation of LA volume (echocardiography and cardiac magnetic resonance) and found high specificity, but low sensitivity of ECG‐derived criteria for detection of LAE …”
mentioning
confidence: 99%
“…The investigators used LA volume index derived by echocardiography as the gold standard method. Rodrigues et al found that individual ECG criteria of LAE in hypertension were specific, but not sensitive, in the diagnosis of LAE. As the reference imaging method for determination of LA volume, they used cardiac magnetic resonance and concluded that ECG should not be used to exclude LAE in the patients with arterial hypertension .…”
mentioning
confidence: 99%
See 1 more Smart Citation